2013
DOI: 10.1007/s11904-013-0158-8
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing: Current Practice and Future Directions

Abstract: New approaches to expanding HIV testing and effective treatment and the wider availability of rapid testing technology have created new opportunities for achieving national and global HIV testing goals. In spite of HIV testing expansion in many settings, growing evidence of the prevention benefits of HIV testing, and the development of new, cost-effective approaches to HIV testing service provision, formidable obstacles to HIV testing expansion persist. Inequitable testing coverage exists within and across cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 62 publications
0
21
1
Order By: Relevance
“…Studies have shown that location of services makes a difference in willingness to seek health services (Cherutich et al, 2013). For instance, studies have provided mixed findings related to getting men to test for HIV in the ANC context, and have suggested that for this testing location to be successful, men must have had previous testing experience elsewhere (Mpairwe et al, 2005;Pool et al, 2001;Spielberg et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that location of services makes a difference in willingness to seek health services (Cherutich et al, 2013). For instance, studies have provided mixed findings related to getting men to test for HIV in the ANC context, and have suggested that for this testing location to be successful, men must have had previous testing experience elsewhere (Mpairwe et al, 2005;Pool et al, 2001;Spielberg et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Another study of African American men showed a preference for medical facilities or, for those without a primary physician, for communitybased or clinic-based settings (Petroll et al, 2009). Given the barriers to VCT uptake among men, there is a need to expand and routinize HIV testing for men in various settings in order to identify new infections and initiate antiretroviral therapy (Cherutich, Bunnell, & Mermin, 2013).…”
mentioning
confidence: 99%
“…Despite the expansion of HIV testing and treatment, major barriers remain at the level of the patient, at health care provider and at institutional/policy (Deblonde et al, 2010). Health policies concerning transwomen are still unresolved (Cherutich, Bunnell, & Mermin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…HIV rapid tests (RTs) have been widely adopted mainly to increase the number of people who are aware of their HIV status and to provide opportunities for faster linkage to care and treatment for those infected [1][2][3]. RTs are simple and easy to use, can be performed on different sample types, have fast result turn-around times (usually less than 30 min), and can be used in many settings since they do not require sophisticated equipment.…”
Section: Introductionmentioning
confidence: 99%